Analisis Pengaruh Ketebalan Plat Dan Sisa Umur Pada Tangki “X” Akibat Pelapukan Oleh Uap Air Laut Di PT. Pertamina Patra Niaga Integrated Terminal Wayame Kota Ambon - La Hamdan; Noce. N. Tetelepta; Edison Effendi (Journal Mechanical Engineering, 2023)
Every oil and gas equipment in the oil and gas industry must have a lifespan, so it is necessary to monitor its performance and condition. Likewise with the stockpile tank, in operation and long use, it is likely to experience a decrease in performance or can be said to experience depletion so that it has the opportunity to cause danger. Plate thickness and remaining tank life play an important role in overcoming weathering due to exposure to seawater vapor. Therefore, PT Pertamina Patra Niaga Integrated Terminal Wayame Ambon City needs to regularly monitor the thickness of the tank plate and perform proper maintenance according to the remaining life of the tank. This aims to maintain the reliability and safety of the "X" tank and avoid greater losses.  Keywords: Oil and Gas Industry, Tank, Plate